Predictors of HIV testing among women experiencing intimate partner violence in the Central Region of Ghana - Beatrice Adwoa Afari; Juliana Yartey Enos; Deda Ogum Alangea; Adolphina Addo-Lartey; Adom Manu (Public Library of Science (PLoS), 2022)
HIV testing, which is important for the control of the HIV pandemic, has been hampered by several factors including Intimate Partner Violence (IPV), resulting in low uptake. This study sought to determine the predictors of HIV testing among women experiencing IPV. Secondary analysis of data generated from a cross-sectional mixed-method unmatched cluster-randomized controlled trial designed to evaluate a multi-faceted community intervention to reduce the incidence of IPV in Ghana was done (N = 2000). Logistic regressions were performed to determine the predictors of HIV testing among women experiencing IPV, using the trial baseline data. The prevalence of HIV testing among women exposed to IPV in the study setting was 42.4%. Less than a third of the respondents (30.2%) had ever used condom and 96.6% had unemployed partners. Age, educational attainment, employment, residence and condom use were found to be significant predictors of HIV testing among women experiencing IPV. Women aged 25-39 years were more than twice as likely to test for HIV (AOR:2.41; 95%CI:1.45-4.02) than those above 45 years. Women with formal education (Junior-High-AOR:2.10; 95%CI:1.42-3.12; Senior-High-AOR:3.87; 95%CI:2.07-7.26); who had ever used condom (AOR:1.42; 95%CI:1.05-1.93); those reporting life satisfaction (AOR:1.44; 95%CI:1.08-1.92); and coastal residents (AOR:1.97; 95%CI:1.45-2.67) were more likely to test for HIV than those who did not and inland residents. However, employed women (AOR:0.66; 95%CI:0.45-0.96) were less likely to test for HIV than unemployed women. Less than half of the women exposed to IPV had tested for HIV. Socioeconomic disadvantages related to age, education, employment, residence and life satisfaction predicted HIV testing among women exposed to IPV. Considering the vulnerability of women experiencing IPV to HIV infection, strategies to improve uptake of HIV testing must tackle contextual socioeconomic factors that hinder access to services.